Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Perumahan Dan Permukiman Kota Serang - Fariz Hidayat; Whina Ratnawati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the influence of work discipline and motivation on employee performance both partially and simultaneously. The object of the study was conducted on employees of the Public Housing and Settlement Area Service of Serang City located at Jl. Brigjen KH Samun No. 7 Kotabaru, Serang District, Serang City, Banten With a total of 65 respondents. The data used in the study are primary data, with a questionnaire as a research instrument. The analysis method used is validity test, reliability test, multiple linear regression analysis, T test, and F test. The results of the study indicate that, Work Motivation has a positive and significant effect on Customer Satisfaction with the regression equation Y = 22.936 + 0.436. Hypothesis testing obtained tcount> ttable or 4.674> ttable 2.007 or significant 0.000 <0.05, this indicates that there is a positive and significant partial influence between Work Motivation on Employee Performance at the Housing and Settlement Service of Serang City. Work Discipline has a positive and significant effect on Purchasing Decisions with the regression equation Y = 16,466 + 0.582X2, the hypothesis test obtained t count> t table or 5.881> t table 2.007 and significant 0.000 <0.05. This shows that there is a positive and significant partial influence between Work Discipline on Employee Performance at the Serang City Housing and Settlement Service. And simultaneously there is an influence of Work Motivation and Work Discipline on Employee Performance with the regression equation Y = 15.147+ 0.168 X1 + 0.450 X2. The coefficient of determination value is 41.8%. The hypothesis test obtained 18.686> F table 3.175. by using a significance limit of 0.05, the value of a significance is 0.000 <0.05. Thus, H03 is rejected and Ha3 is accepted. This indicates a simultaneous positive and significant influence between work motivation and work discipline on employee performance at the Serang City Housing and Settlement Agency.